How the concavity of reproduction/survival trade-offs impacts the evolution of life history strategies. (28th May 2021) - Farrell, Alex P.
ABSTRACT: Previous works using different mathematical techniques, however, show that the concavity of the trade-off relationship can alter the expected life history strategies. Thus we developed a model and found that the concavity of the reproduction–survival curve can still have a large impact on life history strategies in an ecological model with Darwinian evolution.